Tres preguntas sobre guerra y genocidio. - Delrio, Walter (Memoria Americana, 2019)
Throughout the 20th century, the conceptual framework for the study of violence, associated with processes of government construction, colonialism, segregation and extermination, international and liberation wars, has produced a relevant theoretical corpus that proposes new approaches to the concept of war and the genesis of genocide. This paper analyzes how the above mentioned concepts were applied to studying the processes of submission and incorporation of indigenous people in the South American cone. This paper focuses on three central questions regarding the following issues: the definition of social actors, state, agency and the relevance of said concepts for case of the Pampa and the north of Patagonia regions.